STRUKTUR PENYAJIAN TARI JEPIN LANGKAH SERONG DI KOTA PONTIANAK PROVINSI KALIMANTAN BARAT - Augustine, Karina; Ismunandar, Ismunandar; Sanulita, Henny (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe aim of this study is to give the understanding and knowledge about Jepin Langkah Serong dance in Pontianak. This study is about analyzing the structure of the arrangement on Japin LangkahSerong dance in Pontianak, West Borneo. The research design used in this study is descriptive, which is qualitative research design. In this study, the researcher use a choreography approach, the data in this study is the structure of the performances on Jepin Langkah Serong dance in Pontianak, West Borneo. The sources of data are M Yusuf Dahyani , Juhermi Thahir and Anwar Jafar. Techniques used in this study to collect the data are interview, observation, and documentation and the instruments used in this study are interview questions, interview guides, cell phone camera, and a field note.The results of this study on Jepin Langkah dance have the structure of performances which are consists of the initial movements, middle movements and end of the movements. Besides, others elements in dance are floor designs, the composition of the group, a theme, back sound,Â dance properties, makeup and dress, and a venue.The results of this study are expected to be implemented in the Cultural and Arts lesson in class XI Â semesters I.Â Keywords: Structure of Performances, Jepin Langkah Serong Dance, Pontianak